2007
DOI: 10.1126/science.1150755
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Site-2 Protease Family Intramembrane Metalloprotease

Abstract: Regulated intramembrane proteolysis by members of the site-2 protease (S2P) family is an important signaling mechanism conserved from bacteria to humans. Here we report the crystal structure of the transmembrane core domain of an S2P metalloprotease from Methanocaldococcus jannaschii. The protease consists of six transmembrane segments, with the catalytic zinc atom coordinated by two histidine residues and one aspartate residue approximately 14 angstroms into the lipid membrane surface. The protease exhibits t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
249
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(259 citation statements)
references
References 31 publications
8
249
0
1
Order By: Relevance
“…Topological studies suggested that the active site was at or within the plane of the bilayer (Zelenski et al 1999). This inference is supported by recent crystal structure analysis of a bacterial S2P homolog (Feng et al 2007).…”
Section: Site-2 Protease (S2p)supporting
confidence: 64%
“…Topological studies suggested that the active site was at or within the plane of the bilayer (Zelenski et al 1999). This inference is supported by recent crystal structure analysis of a bacterial S2P homolog (Feng et al 2007).…”
Section: Site-2 Protease (S2p)supporting
confidence: 64%
“…In these ways, removal of the periplasmic domain transforms RseA into a substrate of RseP. In the case of presecretory proteins, removal of the large mature domains by Lep might facilitate effective access of SPs to the recessed intramembrane active site of RseP (29). This regulation might also require elements in the enzyme RseP itself.…”
Section: Discussionmentioning
confidence: 99%
“…1) (Rawson et al 1997;Feng et al 2007). Site-2 cleavage releases the NH 2 -terminal domains of the SREBPs from membranes, allowing them to enter the nucleus and activate transcription of their target genes (Fig.…”
Section: Regulation Of the Srebp Pathway In Cultured Cells Regulated mentioning
confidence: 99%